Les 32 plus grandes agglomérations du monde : comment l’urbanisation repousse-t-elle ses limites ? - Cathy Chatel; François Moriconi-Ebrard (Confins)
The classification of the largest agglomerations in the world, called megacities, proposed by the UN is supported by countless scientific or non-scientific publications. Yet the statisticians who make these lists do not conceal the existence of serious problems of comparability due to the fact that the multilateral organization can legally only compile heterogeneous national data communicated to them by the Member States. The use of a true statistical and spatial definition rigorously applied to all the agglomerations of the world gives to see a very different hierarchy. In 2010 - the last year for which the data are reliable - the Planet is home to 32 agglomerations with more than 10 million inhabitants, bringing together 9.4% of the world's population. After explaining the definition, methodology and sources used, the article shows the overwhelming weight of Asia in this area. It then explains the processes of recent emergence of these urban organisms, emphasizing conditions of development that call upon two fundamental notions proposed useful for understanding the phenomenon: that of updating the urban or rural peripheral environment of megacities, and that of regional demographic capital. These processes ultimately show that the number and size of megacities in the world, which has increased dramatically since the 1950s, is expected to double by 2040 but to stabilize thereafter.